Self-Efficacy and Declines Over Time in Attachment Anxiety During the Transition to Parenthood. Issue 5 (July 2021) - Arriaga, Ximena B.; Eller, Jami; Kumashiro, Madoka; Rholes, W. Steven; Simpson, Jeffry A.
Attachment anxiety can decline in relationships but little is known about how or why. A new framework—the Attachment Security Enhancement Model (ASEM)—suggests that what allays current (momentary) insecurity may not necessarily reduce attachment anxiety across time. This article differentiates momentary versus extended attachment processes by examining concurrent versus longitudinal associations. Cohabitating partners ( N = 137 couples) were examined over a 2-year period as they became first-time parents, a transition that could change attachment tendencies. Consistent with ASEM predictions: (1) Anxiously attached spouses who perceived more proximal and sensitive reassurance from their partners felt less concurrent attachment anxiety but not less anxiety across time, and (2) attachment anxiety declined across time when spouses derived personal competence and self-efficacy from their new parenting role. These results document an important distinction between mitigating insecure thoughts and feelings that might reinforce attachment anxiety, versus encountering new experiences that may actually revise chronic insecurity.